2012
DOI: 10.1124/jpet.112.196964
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Induced Renal Injury in Rats Is Attenuated by Suramin

Abstract: Progression of hyperglycemia-induced renal injury is a contributing factor for diabetic nephropathy (DN)-induced end-stage renal disease (ESRD), and development of novel therapeutic strategies that act early to prevent progression of DN and ESRD are important. We examined the efficacy and mechanism(s) of suramin on hyperglycemia-induced renal injury before development of overt histological damage. Two groups of male Sprague-Dawley rats received streptozotocin (STZ) and one group received saline. Three weeks la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
4
16
0
Order By: Relevance
“…Hyperglycemia-induced activation of proinflammatory mediators like NF-κB is part of the pathogenesis of DN [7], [16], [17], [18], [19]. The active and proinflammatory form of NF-κB, phosphorylated-p65, increased in both 9 and 17 week old db/db mice when compared to 9 and 17 week old db/m mice ± suramin (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Hyperglycemia-induced activation of proinflammatory mediators like NF-κB is part of the pathogenesis of DN [7], [16], [17], [18], [19]. The active and proinflammatory form of NF-κB, phosphorylated-p65, increased in both 9 and 17 week old db/db mice when compared to 9 and 17 week old db/m mice ± suramin (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, COL1A2 is associated with tubulointerstitial fibrosis (25). In this study, the levels of renal MCP-1 and COL1A2 mRNA expression increased with age in THM.…”
Section: Discussionmentioning
confidence: 63%
“…In this case, they clearly demonstrated that liquid chromatographytandem mass spectroscopy-based analysis revealed increases in urinary proteins that are early indicators of DN (e.g., cystatin C and peroxiredoxin-1) in the STZ group, which were blocked by suramin. 41 In conclusion, we focus on renal tissue sample but not urine sample. This is the reason why the opposite trend in Prdx1 expression between renal tissue and urine.…”
Section: Discussionmentioning
confidence: 99%